Batting last as a home advantage factor in men's NCAA tournament baseball - Bray, S. R.; Obara, J.; Kwan, M. (Journal of Sports Sciences, 2005)
In baseball and softball, there is a rule that allows the home team to have the last at-bat and thus the final opportunity to win the game. However, in tournament play, this rule is often set aside and, instead, batting order is decided by other means (e.g. tournament rules, the flip of a coin). The purpose of this study was to examine the impact of the batting last rule on game outcome in NCAA men's regional tournament baseball. It was hypothesized that host (i.e. home) teams would win a greater percentage of the games in which they batted last compared with when they batted first. This hypothesis was not supported. Closer examination of the last inning of play showed home teams were no more likely to have won the game during their last bat than visitors playing other visitors. The results suggest that the batting last rule contributes minimally, if at all, to home advantage in NCAA tournament baseball.